Controlled Atomic Layer Deposition of Aluminum Oxide to Improve the Performance of Lithium–Sulfur Batteries. Issue 5 (4th February 2020) - García, Sarai; Leonet, Olatz; Azaceta, Eneko; Gómez, Iñaki; Reifs, Antonio; Blázquez, J. Alberto; Knez, Mato
Abstract : The high capacity of sulfur makes lithium–sulfur (Li–S) batteries the most promising next‐generation battery systems. With a significantly higher theoretical specific energy than conventional lithium‐ion batteries, this technology is intensely investigated. However, currently used cathodes have some critical drawbacks which affect the performance of Li–S batteries. Atomic layer deposition (ALD) demonstrates its power for solving some emerging issues in energy‐storage systems. The application of alumina (Al2 O3 ) to the cathode surface improves the morphology and/or chemistry, providing a solution for some of the most common issues of Li–S batteries. Herein, the cathode of Li–S batteries is coated with alumina by ALD. In addition, the optimal parameters for ALD application to sulfur‐based electrodes are reported. It is demonstrated that alumina deposition results in an improved capacity of the system. The process temperature plays an important role, in particular for few‐cycle ALD processes, aiding better cell performance. Higher numbers of ALD cycles, especially at elevated process temperatures, result in considerable sulfur loss, which significantly lowers the cell performance. Cathodes coated with alumina at low process temperatures and with low numbers of ALD cycles are promising alternatives for conventional Li–S cathodes as they increase the capacity of the system considerably. Abstract : Thin films are deposited by atomic layer deposition (ALD) on the cathode of lithium–sulfur batteries, increasing the capacity of the system by 50%. The optimal parameters, ALD cycles, and process temperatures are chosen for alumina deposition, which are cost effective, time efficient, and improve the performance of the selected energy‐storage systems.